Fish oil replacement in rainbow trout diets and total dietary PUFA content : I) effects on feed efficiency, fat deposition and the efficiency of a finishing strategy - Thanongsak Thanuthong; David Francis; Shyamalie Sendadheera; Paul Jones; Giovanni Turchini (2011)
Fish oil replacement in rainbow trout diets and total dietary PUFA content : I) effects on feed efficiency, fat deposition and the efficiency of a finishing strategy